PEDAGOGICAL AND PSYCHOLOGICAL OPPORTUNITIES FOR PREVENTING YOUTH FROM THE INFLUENCE OF DESTRUCTIVE IDEAS - Umirov Azamat Abdinazarovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents pedagogical and psychological opportunities to prevent the impact of destructive ideas on young people and recommendations for shortcomings in education and measures to eliminate them.